Knowledge, Attitudes and Practices of Waterpipe Smokers in Sulaimani City/ Kurdistan Region of Iraq - Ibrahim Hama Rahim, Bestun; M. Ibrahem, Abdulrahman; Mustafa Kamal, Niaz (Kurdistan Journal of Applied Research, 2018)
Waterpipe smoking is a global phenomenon, particularly among youths and young adults. This practice is rising in the Middle East countries. Waterpipe comprises many chemical toxins as cigarette smoke. Waterpipe smoking can cause several health problems. A descriptive case-series study was performed from 10th of October 2017 to 20th of December 2017 in eight waterpipe cafeterias in Sulaimani city. The current study involved 230 waterpipe smokers. A structured questionnaire was used to collect data. P-value ?0.05 was used to show a level of significance. The age range of the waterpipe smokers was 16-39 years with the mean age was 24.63 years. The age distribution was a sharp peak in the age group of 21 to 25 years, over two fifths (40.9%) of the study subjects lay in this age group. The waterpipe smoking was higher in the individuals with high education level (52.2%). Regarding the participants’ occupations, the frequency of the waterpipe smoking was higher among self-employment. Over two-thirds of participants (68.7%) were unmarried. The main motives for waterpipe smoking were life pressures, pleasurable experience, and habit (31%, 27%, and 25% respectively). The majority of participants had a good knowledge about the negative health effects of waterpipe smoking. Approximately half of the participants (48.3%) possessed waterpipe at home, over two thirds (68.3%) of subjects preferred smoking waterpipe with their friends, half of the respondents (50.0%) preferred smoking waterpipe at the cafeteria. Likewise, over half of participants (51.3%) smoked waterpipe every day. The main reason for the intention to quit waterpipe was a health concern.